The current and future global distribution and population at risk of dengue - Messina, Jane P.; Brady, Oliver J.; Golding, Nick; Kraemer, Moritz U. G.; Wint, G. R. William; Ray, Sarah E.; Pigott, David M.; Shearer, Freya M.; Johnson, Kimberly; Earl, Lucas; Marczak, Laurie B.; Shirude, Shreya; et al. (Nature microbiology, 2019)
Statistical mapping techniques provide insights into the current geographical spread of the mosquito-borne dengue virus infection and predict changes in the areas that will be environmentally suitable to the virus for the years 2020, 2050 and 2080.
Gesehen am 16.11.2019